The effects of stand characteristics on reindeer lichens and range use by semi-domesticated reindeer - Helle, T.; Aspi, J.; Kilpelä, S.-S. (Rangifer, 1990)
The study was carried out in Kuusamo (66°15'N, 29°05'E) and Inari (68°30'N, 28°15'E), northern Finland, where 24 and 22 Scots pine stands were studied respectively. Clear-cutting (logging residue) caused a decline in lichen biomass for some few years, but otherwise the age of the stand had no effect upon lichen biomass. Instead, a positive correlation was found between litter/logging residue and the mean height of lichens; in Kuusamo, logging residue decreased significantly with the age of the stand. Grazing pressure in terms of fecal group density increased with the age of the stand. The preference of old forests came visible also as a lower mean height of lichens, which eliminates the possibility that the preference of old forests is associated only to the use of arboreal lichens. In Inari, grazing pressure sharply increased after the stand had reached the age of 100 years despite scarce litter/logging residue and fair lichen ranges in younger forests; there prevailed a negative correlation between stand density and grazing pressure. It has been suggested that there might be three main reasons for reindeers preferring old forests: 1) hardening of the snow (because of winds) on clear-cut areas, 2) logging residue preventing digging for the food beneath the snow, and 3) poor visibility in young pine stands (Inari) which might increase predation risk.